Методы косвенного контроля эксцентричности воздушного зазора асинхронных електродвигателей - Хоменко, Игорь Васильевич; Тихонравов, С. Н. (НТУ "ХПИ", 2009)
В результате экспериментальных и теоретических исследований влияния эксцентричности воздушного зазора на уровни токов от высших гармоник магнитного поля разработан ряд взаимодополняющих методов косвенного контроля статического эксцентриситета.

Experimental and theoretical researches of an air gap eccentricity and its influencing on current harmonics induced by magnetic field are fulfilled for an asynchronous motor. A number of indirect complementary methods of eccentricity control is developed.
Indirect methods used for control of eccentrisity in the air gap of asynchronous motor
Keywords: асинхронные электродвигатели; воздушный зазор; эксцентричность; магнитное поле; ток; методы контроля; asynchronous motor; air gap; eccentricity; magnetic field; harmonics; control methods